Understanding and mitigating settlement in gypseous soils: A comprehensive study on the role of saturation and soil stabilization techniques - Al-Assady, Fadhl Abbas Ahmed; Alkifaee, Abdulazeez A. Azeez (Edelweiss Applied Science and Technology, 2024)
This study examines the influence of saturation levels and soil additives on the load-settlement properties of gypseous soils, a significant geotechnical concern in regions like Iraq. The study analyzes the deficiencies of conventional oedometer testing, which often fail to adequately represent the true unsaturated conditions prevalent in these soils. The research investigates the impact of varying matric suction (Ψ) values on the compressibility of untreated, cement-treated, and CKD-treated gypseous soils. A modified oedometer apparatus, engineered to control and quantify matric suction, was used to replicate diverse moisture conditions. The experimental program investigated soils with varying gypsum contents (8.8%, 12.66%, and 30%), reflecting the diversity of gypseous soils seen in the field. The findings demonstrate that increased saturation levels significantly enhance settling in gypseous soils. As matric suction increases, settlement is markedly reduced due to elevated soil suction pressure and enhanced effective stress. The findings underscore the importance of unsaturated conditions in improving the load-bearing capacity of these soils. The study illustrates the advantageous impacts of cement and CKD treatments in reducing settling. The effectiveness of these methods is particularly apparent in partially saturated environments, emphasizing the need of including matric suction into design considerations. This research improves understanding of the complex behavior of unsaturated gypseous soils. The findings have practical importance for geotechnical engineering, including foundation design, ground improvement methods, and the development of effective solutions for settlement issues in areas with high gypsum concentrations.